2019
DOI: 10.1139/cjfas-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference from the conditional genetic stock identification model

Abstract: Genetic stock identification (GSI) estimates stock proportions and individual assignments through comparison of genetic markers with reference populations. It is used widely in anadromous fisheries to estimate the impact of oceanic harvest on riverine populations. Here, we provide a formal, explicit description of Bayesian inference in the conditional GSI model, documenting an approach that has been widely used in the last 5 years, but not formally described until now. Subsequently, we describe a novel cross-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 33 publications
1
112
0
Order By: Relevance
“…Genotypes from potential source species were used to estimate allele frequencies that compose a reference against which data from individuals of unknown species were assessed (Clemento, Crandall, Garza, & Anderson, 2014;Pella & Milner, 1987), with maximum-likelihood or Bayesian methods (Pella & Masuda, 2001;Smouse, Waples, & Tworek, 1990). Here, genotypes from adults of these four species (kelp, copper, black-and-yellow and gopher rockfishes) were included in the genetic stock identification (GSI) baseline and each adult rockfish genotype was assigned a likelihood of being from each of these species using the self-assignment function in the software gsi _ sim (Anderson, Waples, & Kalinowski, 2008;Moran & Anderson, 2018). Adult rockfishes are typically identifiable by colour and morphology, and the gsi _ sim assignments confirmed field identifications and detected any misidentified fish.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes from potential source species were used to estimate allele frequencies that compose a reference against which data from individuals of unknown species were assessed (Clemento, Crandall, Garza, & Anderson, 2014;Pella & Milner, 1987), with maximum-likelihood or Bayesian methods (Pella & Masuda, 2001;Smouse, Waples, & Tworek, 1990). Here, genotypes from adults of these four species (kelp, copper, black-and-yellow and gopher rockfishes) were included in the genetic stock identification (GSI) baseline and each adult rockfish genotype was assigned a likelihood of being from each of these species using the self-assignment function in the software gsi _ sim (Anderson, Waples, & Kalinowski, 2008;Moran & Anderson, 2018). Adult rockfishes are typically identifiable by colour and morphology, and the gsi _ sim assignments confirmed field identifications and detected any misidentified fish.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we exploit known ancestral populations in a supervised learning model in ADMIXTURE (Alexander & Lange, ) and use the EM algorithm for estimating the ancestry coefficient matrix Q . In addition, we compare our method with two recent population assignment techniques, RUBIAS (Moran & Anderson, ) and AssignPOP (Chen et al, ). These methods are implemented in R packages radmixture, RUBIAS and AssignPOP respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we compare BONE with three population assignment methods: commonly used ADMIXTURE (Alexander, Novembre, & Lange, ), along with two recently published methods ‘RUBIAS’ (Moran & Anderson, ) and ‘AssignPOP’ (Chen et al, ) using both simulated and real data. ADMIXTURE, RUBIAS and AssignPOP are implemented in R packages radmixture, RUBIAS and AssignPOP, respectively, and are publicly available at CRAN (The Comprehensive R Archive Network).…”
Section: Introductionmentioning
confidence: 99%
“…We decided to use Oncor for this study based on two main criteria; (a) It is/has been widely used in GSI studies and (b) is user‐friendly and has several built‐in simulation tests (e.g., 100% simulation and self‐assignment‐test) very commonly used in published GSI studies. Several other computer programs developed for GSI analysis exists, e.g., cBayes (Neaves, Wallace, Candy, & Beacham, ) , GeneClass2 (Piry et al, ) , Rubias (Moran & Anderson, ) and Spam (Debevec et al, ), but a comparison of outcomes from different software was beyond the scope of this study. Furthermore, when evaluated in other studies, Oncor has been shown to perform equal to several of those alternative software (Debevec et al, ; Griffiths et al, ; Ikediashi, Billington, & Stevens, ; Vaha et al, ).…”
Section: Methodsmentioning
confidence: 99%